Viral Infection in Glioblastoma: Immunohistochemistry in Detection of Cytomegalovirus, Epstein-Barr and Herpes Simplex – 1 Virus - Nenad Koruga; Tatjana Pekmezović; Ilijan Tomaš; Jasmina Rajc; Alen Rončević; Anamarija Soldo Koruga (Southeastern European Medical Journal)
Introduction: Glioblastoma (GB) is the most aggressive glial tumor of the brain with a dismal prognosis. Studies conducted during the last two decades highlighted neurotropic viruses as a risk factors involved in development of glioblastoma. Authors present an immunohistological study conducted in a single center on sixty-three archive paraffin-embedded samples of GB.